LOCAL GOVERNMENT MANAGEMENT IN HANDLING COVID-19 IN KARIMUN DISTRICT - Aprizal, Aprizal; Indrayani, Indrayani; Azwandi, Azwandi; Rahman, Abdurr; Pasaribu, Sapta (RADJA PUBLIKA, 2022)
Covid-19 is a viral outbreak that is sweeping the world, Covid-19 is a virus outbreak that is transmitted from one person to another. This virus is the biggest problem that even big countries have to face, the COVID-19 virus has paralyzed the world's economy with the outbreak of the virus, of course, being an obstacle to the process of providing goods and services on the domestic and international scene. In Indonesia, the increase in the number of positive COVID-19 patients is moving fast. So, the government enforces the PSBB regulations as a preventive measure, of course this is also done by the Regency and City governments, one of which is Karimun Regency. The Karimun Regency Government also plays an active role in issuing policies to reduce the spread of the Covid-19 virus, while this strategy must have been taken into account with existing conditions.